The Role Of The Ustrushana Region In Transregional And Cultural Relations On The Great Silk Road - Abduraimov Dilshod Sultanovich (Genius Journals, 2024)
This article shows the cultural, political and trade relations and interaction of Ustrushona and the development of the Great Silk Road at the height of its prosperity, and the political, cultural and trade relations of Central Asia and other regions also gained importance. passed.
Keywords: Ustrushona; China; Sugdiyana; Development